GAYA BAHASA DAN DIKSI DALAM LIRIK LAGU MARIGOLD KARYA AIMYON : KAJIAN STILISTIKA - Putra, Gusti Made Mega Adi; Andriyani, Anak Agung Ayu Dian; Aritonang, Betty Debora (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
This research is about the style of language and diction in the lyrics of the song Marigold by Aimyon. The data used were obtained from the lyrics of a song by Aimyon entitled Marigold. The purpose of this research is to find out and understand the use of style of language and diction in the lyrics of Aimyon's Marigold song. The theory used is the stylistic theory by Burhan Nurgiyantoro (2014). Data collection methods and techniques used, namely obeservation method. Meanwhile, the data analysis methods and techniques used were descriptive qualitative methods. Methods of presentation of data analysis results using informal methods. The results of this research there are 2 style and 6 dictions contained in the lyrics of the analyzed songs. The style contained in this song consists of 1 hyperbole, 1 repetition, 5 denotative diction, and 1 connotative diction.